Process evaluation of a complex intervention to optimize quality of prescribing in nursing homes (COME-ON study) - Anrys, Pauline (Implement Sci, 2019)
BACKGROUND: The COME-ON study was a cluster-controlled trial of a complex intervention that consisted of a blended training program, local interdisciplinary meetings, and interdisciplinary case conferences in Belgian nursing homes. The intervention was associated with significant improvements in the appropriateness of prescribing. The aims of this study were to describe the implementation of the intervention and to explore the experiences of participants, for the purpose of identifying factors associated with implementation and perceived impact and to draw lessons for future implementation. METHODS: We performed a mixed-method process evaluation. Questionnaires and reports were used to collect quantitative data on implementation and experiences from the 24 NHs and participating healthcare professionals (coordinating physicians, general practitioners, pharmacists, and nurses) in the intervention group. Multidisciplinary focus groups focusing on factors associated with implementation and perceived impact were conducted in 11 NHs. RESULTS: Overall, the rate of implementation and the satisfaction of participants were good, despite some variability between NHs and HCPs. Although perceived impact on nursing home residents varied, most participants perceived a positive impact for themselves. Factors associated with implementation and perceived impact were identified at different levels: intervention, healthcare professionals, organization, and external context. The interdisciplinary and face-to-face approaches were recognized as key elements for the success of the intervention, despite organizational constraints. The attitude of general practitioners was identified both as a barrier to and a facilitator for implementation and its success. The professional role and competency of the pharmacist influenced perceived impact. The pre-existing relationships between HCPs and the presence of a leader facilitated implementation and perceived impact. Remuneration was deemed necessary for the study and for future implementation. CONCLUSIONS: Overall, the intervention, and more specifically its interdisciplinary aspect, was well implemented and appreciated by HCPs. This probably contributed to the positive effect on the appropriateness of prescribing. Future implementation must take into account the various factors found to affect implementation and perceived impact, in order to maximize effect and sustainability. Trial registration Current Controlled Trials ISRCTN66138978; registered 18 November 2015, retrospectively registered, https://www.isrctn.com/ISRCTN66138978